Physiological quality of rice seeds as a function of different doses of the insecticide cyantraniliprole (Colloquium Agrariae. ISSN: 1809-8215, 2023)
The seed is one of the main agricultural inputs and its quality is one of the key factors for success in rice cultivation. The objective of this work was to evaluate the physiological quality of rice seeds with different doses of the insecticide cyantraniliprole and its performance during storage of rice seeds. Rice seeds of the cultivar IRGA 424 RI treated at doses 0 (control), 10, 20, 40, 60, 80 and 100 mL of the product for each 100 kg of seeds were used. Evaluations were performed during storage periods 0, 60, 90, 135 and 180 days after treatment. Seed quality was monitored through the germination test, cold test and emergence. Under the conditions in which the work was carried out, we can conclude that: cyantraniliprole at doses of 60, 80 and 100 ml/100 kg of seeds provides greater germination when the seeds are not stored, however the dose of 60 mL/100 kg showed higher percentages of germination in other storage periods. For the cold test, cyantraniliprole in all doses was superior to the control without treatment and in the doses 60 mL/100kg of seeds it was superior in the storage times 0, 135 and 180 days, already in the storage periods 60 and 90 days the dose of 60 mL/100kg did not differ from the dose of 80 mL/100 kg. For the emergence of seedlings, the treatment with the insecticide at a dose of 60 mL/100kg of seeds was superior to the others, except for the storage period of 135 days.